Parenting advantages of emerging market multinationals (EMNCs) in luxury fashion retailing. Issue 1 (8th July 2021) - Bai, Huifeng; He, Weijing; Shi, Jin; McColl, Julie; Moore, Christopher
Abstract : Purpose: This empirical research, adopting an international retailing perspective, aims to examine the parenting advantages offered by emerging market multinationals (EMNCs) in luxury fashion retail sector. Design/methodology/approach: The researchers adopted a qualitative case study, and the qualitative data were collected through ten semi-structured interviews with senior managers. Findings: It is a win–win situation for the EMNCs as parent groups of Western luxury fashion brands, as the EMNCs can access critical assets including advanced brand management expertise, retailing know-how, and the services skills needed for higher income consumers. Meanwhile, the subsidiary brands benefit from a high degree of autonomy, intra-group resource utilisation, a competitive brand portfolio and most importantly economies of scales in the value chain, particularly in production. The perceived risks of EMNCs ownership include potentially restricted autonomy and the uncertainty over corporate development activities in the future, as well as the risks of diluting brand image caused by the inconsistency between country of origin and country of ownership. Research limitations/implications: Very few EMNCs have moved into luxury fashion retailing to date, which means that the sampling frame was small. The findings were generated from China, which is perceived to be of considerable psychic distance in terms of culture and policies compared to other emerging markets that have been heavily influenced by colonialism. Practical implications: This paper suggests that practitioners, particularly EMNCs, support their subsidiary luxury fashion brands through parenting advantages and develop their own high-end fashion brands through internationalisation. Originality/value: This empirical study contributes to the current international retailing literature by offering in depth insights of parenting advantages offered by EMNCs in luxury fashion retailing. It also enriches the EMNC literature, which has mainly adopted an international business scope, by extending this understanding into luxury fashion retailing.